Application of Functionalized Multi-Walled Carbon Nanotubes for Growth Enhancement of Mustard Seed Germination - Agus Subagio; Erma Prihastanti; Ngadiwiyana Ngadiwiyana (Universitas Gadjah Mada, 2020)
Multi-walled carbon nanotubes (MWCNTs) are one of the nanomaterials that can be applied to agriculture. This work investigates the beneficial effects of MWCNT function on mustard plants. In this study, the material of MWCNTs is functionalized with nitric acid to attach the carboxylic group onto the tube wall. The functionalized MWCNTs were characterized by SEM, TEM, XRD, and FTIR. The MWCNT diameter produced ranges from 20 to 50 nm and the inner diameter is 5 to 10 nm at the pyrolysis temperature of 900 °C. It was found that crystallites of the MWCNTs have (002) and (100) directions. There is a weak peak in MWCNTs prior to the functionalization process due to the presence of metal carbide (Fe3C), which serves as an active catalyst. FTIR results clearly indicate the presence of hydroxyl and carboxylic groups. These functionalized MWCNTs were dispersed into distilled water with various concentrations at 25, 50 and 75 µg/mL. By utilizing an immersion time of 24 h, mustard (Brassica juncea) seeds were soaked in each functionalized and non-functionalized MWCNT solution. Functionalized MWCNT solution at a concentration of 50 µg/mL was found to affect the growth of mustard seeds more significantly.